DEVELOPING INTERACTIVE MEDIA FOR LEARNING MATHEMATICS PYTHAGORAS MATERIALS WITH CONTEXTUAL APPROACH FOR GRADE 8th JUNIOR HIGH SCHOOL - Ceria Andespi; Bambang Sumarno Hadi M. (Jurnal Pedagogi Matematika, 2016)
This research aims to develop interactive learning media using contextual approach for Pythagoras Theorem material for grade VIII students of Junior High School. This developed media was using ADDIE method which consist of the following steps: analyze, design, development, implement and evaluation.  The data from this research were in the form of quantitative data through learning media evaluation questionnaire by mathematics teacher of junior high school, students responses questionnaire and test results and were in the form of qualitativ data through feedback and suggestions on the developed learning media product appropriate with developing procedure according to media and materials from expert judgment.  Overall, the developed media was suitable media because it fulfilled valid and practical criteria as follows: (1) the materials on the quality of content and the goal aspect got the final score 91.75%  and 86.25% for instructional quality, (2) the materials on the technical quality aspects got 89% so it is categorized as valid media, (3) the trial result got final score 93.33% and the media is categorized as a very practical media.   Keywords: interactive learning media, pythagoras theorem